Real-time evaluation of antibacterial efficacy using bioluminescent assays for Pseudomonas aeruginosa and Staphylococcus aureus - Patil, Manali; Luo, Congyu; Petruk, Ganna; Petrlova, Jitka; Schmidtchen, Artur; Puthia, Manoj (Frontiers in Microbiology, 2025)
The emergence of antibiotic resistance necessitates effective strategies for evaluating antimicrobial agents. Bioluminescent bacteria, either naturally occurring or engineered with modified reporter genes like bacterial luciferase, provide real-time assessment of bacterial viability through light emission. We investigated the antibacterial effects of cefotaxime and doxycycline using bioluminescent strains of S. aureus and P. aeruginosa, combining optical density measurements with bioluminescence monitoring. Treatment with cefotaxime resulted in a significant reduction of the bioluminescent signal in P. aeruginosa compared to untreated controls, while doxycycline induced a delayed growth curve. Both antimicrobials demonstrated strong efficacy against S. aureus, as evidenced by decreased bioluminescence signals. Results from bioluminescence assays and classical minimum inhibitory concentration and minimum bactericidal concentration methods showed consistent alignment, validating the bioluminescence approach. This study demonstrates that bioluminescence-based methods offer a reliable, real-time alternative to traditional bacterial viability assays for evaluating antimicrobial efficacy.